Using Pumpkin Pulp to Make Cooked Sausage from Beef Enriched with Β-Carotene - Irina A. Kadnikova, Elena V. Skripchenko, Tatyana K. Kalenik (International Journal of Advanced Science and Technology, 2020)
This paper is written to explore the possibility of using a bioactive agricultural raw material (Ulybka pumpkin pulp) to produce cooked sausages for optimizing their functional and technological properties and chemical composition. The object chosen for enrichment was the “Govyazhya” cooked sausage produced by local meat processing plant OOO “Ratimir” (Vladivostok) according to TC 9213-003–50831611–2014. The functional and technological properties of the model stuffing systems were characterized by their overall moisture-binding, water-retaining, and fat-retaining capabilities (MBC, WRC, FRC). The physico- chemical quality indicators of the samples of meat and plant sausages were analyzed, including mass fractions of proteins, fat, moisture, sodium nitrite, sodium chloride, and carotenoids. The plant component content in the cooked beef sausage was determined by adding pumpkin pulp in amounts of 5, 10, and 15 % to the meat system to replace the same respective fractions of water. The comparative data on the quality indicators of sausage products with pumpkin pulp are presented. Ulybka pumpkin was used as a source of carotenoids. The formulation and production process flow of the cooked sausage with pumpkin were elaborated and its physical and chemical, functional and technological, and organoleptical properties studied. The shelf life of the cooked sausage with pumpkin packaged in Amiflex shell are stored at 0 to 5 оС is 45 days. The addition of pumpkin pulp to the meat stabilizes the product’s technological characteristics and allows making meat products with properties close to the requirements imposed on products with a functional food ingredient. The sausage with pumpkin has a lower residual sodium nitrate content compared with the reference formulation. One hundred grams of daily eaten cooked sausage with a pumpkin pulp content of 10 % meet the daily human demand for beta-carotene by 26 %. The nutritional and calorific value of the elaborated sausage products are 180 to 189 kcal and 752.4 to 790.02 kJ, respectively, which meets the requirements on products of low calorific value.